cAMP Responsive Element Modulator (CREM) α Mediates Chromatin Remodeling of CD8 during the Generation of CD3(+)CD4(−)CD8(−) T Cells - Hedrich, Christian M. (American Society for Biochemistry and Molecular Biology, 2014)
TCR-αβ(+)CD3(+)CD4(−)CD8(−) “double negative” T cells are expanded in the peripheral blood of patients with systemic lupus erythematosus (SLE) and lupus-prone mice. Double negative T cells have been claimed to derive from CD8(+) cells that down-regulate CD8 co-receptors and acquire a distinct effector phenotype that includes the expression of proinflammatory cytokines. This, along with the fact that double negative T cells have been documented in inflamed organs, suggests that they may contribute to disease expression and tissue damage. We recently linked the transcription factor cAMP responsive element modulator (CREM) α, which is expressed at increased levels in T cells from SLE patients and lupus prone MRL/lpr mice, with trans-repression of a region syntenic to the murine CD8b promoter. However, the exact molecular mechanisms that result in a stable silencing of both CD8A and CD8B genes remain elusive. Here, we demonstrate that CREMα orchestrates epigenetic remodeling of the CD8 cluster through the recruitment of DNA methyltransferase (DNMT) 3a and histone methyltransferase G9a. Thus, we propose that CREMα is essential for the expansion of double negative T cells in SLE. CREMα blockade may have therapeutic value in autoimmune disorders with DN T cell expansion.